The Role of School Administrators in Improving the Quality of School Management in the Digital Era - Dhiba, Niar Farah; Triwiyanto, Teguh; Maisyaroh, Maisyaroh (Universitas Negeri Malang, 2024)
The role of administrative staff in school management in the digital era is still relatively minimal. The role of administrative staff is an important part of the school management system, which is often overlooked. In the digital era, this role is even more important as they have to help operate various digital systems that support school management. The purpose of this study is to describe the multifaceted role of administrative staff in utilizing technology to improve the quality of school management. This research uses the desk research method and focuses on analyzing literature and secondary materials related to the research topic. The data source of this research is literature or documents relevant to the research topic. The data used is secondary data that already exists and is available to the public. Data analysis is carried out through the process of reading, synthesizing, and understanding the information contained in the data sources. The adoption of digital technology in school management leads to increased efficiency, better decision-making, increased transparency and improved quality assurance, while it also presents challenges that need to be addressed for successful adoption. The important role of administrative staff in utilizing technology to improve school management, enhance decision-making, and ensure quality education, ultimately leading to better outcomes for students and the institution as a whole.